Draft Five Year Plan 1978-83 Health and Family Planning Government of Madhya Pradesh - Planning Commission (Planning Commission, 1978)
The State of Madhya Pradesh, divided into 45 districts, has an area of 442841 sq.kms. and a population of 4.16 crores (1971 Census) - the rural urban ratio being 84:16. The estimated projected population in 1976 was 4.71 crores and is likely to be 5.20 crores in 1981. The percentage of Scheduled Castes and Scheduled tribes of total population is estimated at 13.09 and 20.14, respectively.
Government of Madhya Pradesh, Planning, Economics and Statistics Department